The Grotesque in Roman Love Elegy - Pietropaolo, Mariapia (University of Cambridge ESOL Examinations, 2020)
Cover -- Half-title -- Title page -- Copyright information -- Dedication -- Contents -- Preface -- Acknowledgements -- List of Abbreviations -- Chapter 1 Premises and Expectations of the Elegiac Grotesque -- Premises -- Classical Framework -- Modern Framework -- Genre and Textual Coordinates of the Elegiac Grotesque -- The Non-Elegiac Grotesque -- Chapter 2 Context and Prehistory of the Elegiac Grotesque -- The Lucretian Corporification of Love -- Lucretius on the Physiology of the Beloved -- Catullus on the Sordid Side of Love Affairs -- Catullus' Punitive Grotesque -- Chapter 3 Cynthia and the Grotesque Ethos -- Cynthia's Uncanny Apparition -- The Ethos of Ambivalence -- Elegiac Cacophony -- Chapter 4 The Ovidian Unmasking of the Elegiac Grotesque -- The Vitium of Love -- The Bald Puella: Amores 1.14 -- The Puella between Beauty and the Grotesque -- Chapter 5 Revolting and Refined: The Aesthetic Function of Acanthis -- The Lena -- The Lena's Song -- Chapter 6 Grotesque Hermeneutics of the Lena in Tibullus and Ovid -- Tibullus' Lena and the Hermeneutical Grotesque -- The Grotesque Ethos of the Tibullan Lena -- Dipsas and the Manifestations of the Grotesque -- Chapter 7 The Rival: A Vir Foedus -- The Propertian Rival -- The Tibullan Rival -- The Ovidian Rival -- Chapter 8 Pasiphae and the Allurement of the Grotesque -- Negative Eroticism -- The Literal and the Metaphorical Grotesque -- A Lover's Discourse on Bovine Love -- Bovine Allurement and Mock Sympathy -- Signatus Tenui Nigro: The Bull's Black Spot -- Chapter 9 Ovid's Remedia and the Waning of the Elegiac Grotesque -- References -- Index.